Increased prevalence of Listeria monocytogenes in the faeces of patients receiving long-term H2-antagonists. - Cobb, C; Curtis, G; Bansi, D; Slade, E; Mehal, W; Mitchell, R; Chapman, R (1996)
BACKGROUND: Human listeriosis is an uncommon infection caused by the Gram-positive organism Listeria monocytogenes. OBJECTIVE: To investigate the effects of therapeutic gastric acid suppression on faecal isolation of L. monocytogenes and the incidence of human listeriosis. METHODS: Five stool specimens from each of 20 patients on continuous H2-antagonist therapy and two faecal samples from each of 47 healthy controls were investigated for the presence of Listeria spp. RESULTS: A higher faecal isolation rate of L. monocytogenes was detected amongst the patients (20%) compared with the controls (2.1%) (P < 0.025). All subjects with stools positive for Listeria spp. were female, this sex difference being significant in the patient group (P < 0.0036) compared with controls. No patient, however, developed listeriosis. CONCLUSION: Patients on long-term gastric acid suppressive therapy may be at increased risk of faecal carriage of L. monocytogenes.